Analysis of TheVadility of A Cession Over A Receivables Sale and Purchase Agreement That Was Subject to an Invalid Novation - Bella Fabiola; Akhmad Budi Cahyono (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
In order to guarantee smooth capital turnover, banks would often "withdraw" their capital even if the receivables (often from credit) that they currently own are not yet payable, by selling their receivables, followed by cession. However, in practice this is often problematic. Most of the problems revolving around this practice is that the cession that follows the selling of receivables is conducted not in accordance with applicable laws regarding cession and could therefore backfire and become a problem for the bank in question. The cession of Permata Bank on Debt Assignment Deed (Cession) Number 85 dated 5 May 2017, as stated in the Central Jakarta Commercial Court Decision Number 131/Pdt.SUS-PKPU/2018/PN.Niaga.Jkt.Pst is one of such problematic cessions. On this matter, the assignment of receivables was done through Debt Assignment Deed (Cession) Number 85 dated 5 May 2017, related to a Conditional Receivables Sale and Purchase Agreement that was novated and then amended. This article uses a normative juridical research method. The research specifications used in this study are descriptive analytical. The secondary data used by the author in this study consisted of primary legal materials, secondary legal materials, and tertiary legal materials. The data analysis method used is normative qualitative. The Conditional Receivables Sale and Purchase Agreement is carried out without the transfer of ownership with cession, so that the ownership has not yet been transferred to the buyer. The Novation and Amendment To the Conditional Receivables Sale and Purchase Agreement is also invalid because it was carried out without involving the debtor. So, it can be concluded that the cession of the Conditional Receivables Sale and Purchase Agreement which was later novated and amended is null and void because the cession was made under a receivables sale and purchase agreement that was invalidly novated. Key Words: Cessie, Novasi, Receivables Sale and Purchase Agreement